Expression of Epidermal Growth Factor and Epidermal Growth Factor Receptor Immunoreactivity in the Asthmatic Human Airway - AMISHIMA, MASARU; MUNAKATA, MITSURU; NASUHARA, YASUYUKI; SATO, ATSUKO; TAKAHASHI, TORU; HOMMA, YUKIHIKO; KAWAKAMI, YOSHIKAZU (American journal of respiratory and critical care medicine, 1998)
Chronic airway inflammation, one of the pathophysiologic features of bronchial asthma, is suspected to be responsible for irreversible pathological changes of airways, called airway remodeling. To examine the mechanisms of airway remodeling in asthma, we investigated the expression of epidermal growth factor (EGF) and its receptor immunohistochemically in asthmatic human airways. Airway specimens from seven patients with asthma were obtained from autopsied and surgically resected lungs. Control specimens were obtained from lungs of eight subjects without asthma and other pulmonary complications at autopsy. We stained those specimens by the avidin-biotin-peroxidase complex (ABC) method with anti-human polyclonal EGF antibody and monoclonal EGF receptor antibodies. Three different portions of airways-large bronchi (about 1 cm in diameter), small bronchi (about 3 mm in diameter), and peripheral airways (less than 2 mm in diameter)-were examined. The thickness of the bronchial smooth muscle and basement membrane was significantly greater in the asthmatic airways than in controls. Clear immunoreactivities of EGF were widely observed on bronchial epithelium, glands, and smooth muscle in asthmatic airways. In the controls, the bronchial epithelium and the bronchial glands partially expressed faint EGF immunoreactivity. For the EGF receptor, clear immunoreactivities were also observed on bronchial epithelium, glands, smooth muscle, and basement membrane in asthmatic airways. In control airways, only part of the bronchial epithelium and smooth muscle weakly expressed EGF receptor immunoreactivity. These results suggest a possible contribution of EGF to the pathophysiology of bronchial asthma, including airway remodeling.